ADAPTASI PENAFSIRAN AYAT-AYAT AL-QUR’AN TENTANG PERUBAHAN IKLIM PADA MATERI PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH MENENGAH ATAS (SMA) - Afandi, Irfan (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The study of climate change has disappeared from the curriculum of qur'an hadith material in pai sma subjects. Whereas climate change is a major issue. Even so, with the approach of interpretation of the Qur'an, the study of climate change can be interpreted in the interpretation of verses from the Qur'an as long as it uses the methods that have been known in the Qur'an ulumul. This article seeks to examine and work on a way out of the problem. The infrequent study of this is one of the urgency of this paper. High schools consist of three (3) levels, each of which has been determined by learning outcomes. Class X PAI material revolves around the issue of orders to compete in kindness and work ethic as well as the prohibition of promiscuity and adultery. In pai class X SMA materials, adaptation and integration cannot be done because there is no linkage of verses that allow adaptation of interpretation. Meanwhile, the Learning Outcomes of PAI Material class XI and XII have eight (8) themes, namely critical, science and technology, tolerance, maintaining human life, disasters, exams, love for the homeland and religious moderation. In the material of the Qur'anic verses on critical thinking, science and technology, disasters and exams, adaptation of interpretation and integration of climate change materials can be carried out; But on the material of tolerance, nurturing human life, love of the homeland and religious moderation can not be adapted to interpretation. The reason is not supported by munasabah (linkage) to the material. These materials are related to the relationship between people (hablu minnannas), the love of the homeland and religious life in the context of nation and state. The process of adapting and integrating the material depends largely on the ability of the teacher in mastering the ulumul Qur’an.